Ibn Hisham’s Attitude towards Al-Hufi’s Grammatical Directions for Qur’anic Verses through His BookMughni Al-Labib as an Example - Hessien, Anwer Jamal (Journal of Tikrit University for Humanities, 2024)
The present research deals with Ibn Hisham’s attitude towards Al-Hawfi’s grammatical opinions, especially for some of the Qur’anic verses, in which Ibn Hisham either supports Al-Hawfi with regard to it in his parsing, and what warns of his delusion and desire in his understanding of a specific text. Therefore, he establishes a grammar rule and then invalidates the grammatical side. Consequently, Ibn Hisham added it to that in the introduction to his book, and said:” in it, I traced closed grammatical issues and opened them, and difficult dilemmas that required their formation, so I clarified and revised them, and errors by a group of Arabs, so I alerted them and corrected them, absolutely abiding by Ibn Hisham’s meaning of words and the grammatical significance of articles”. This is done to achieve subjugation of parsing in the service of meaning, including what is compatible with the general context of the text.